(untitled) (Journal of Global Accounting, 2023)
This study assessed the effect of Corporate Attributes (companys’ age and company size) on Earnings Management of non financial firms listed on the Nigeria Exchange limited (NGX). The population of the study covered the ninety-five (95) non-financial firms listed on the Nigerian Exchange Group, covering a period of 11years, (2011-2021). Ex post facto research design was employed, with extensive reliance on secondary data, which include annual reports, corporate website of companies and the Nigerian Stock Exchange Group Fact book. The study used purposive sampling technique to select the sample size of seventy - four (74) non financial firms listed on the Nigerian Exchange Limited. Data collected were tested using Multiple Regression analysis on Statistical Package for Social Sciences (SPSS version 20.0). Empirically, the results revealed that both company size and company size have significant effect on earnings management of non-financial firms in Nigeria. In conclusion, the study established that corporate attributes significantly affect earnings management practices in non financial firms listed on Nigeria Exchange limited (NGX). The study recommended that financial regulatory bodies like Financial Reporting Council and the Securities and Exchange Commission should be proactive in terms of formulation of policies that will help in tightening up security measures prohibiting the serial occurance of these earnings management practices in Nigeria. Government should also on timely basis organize seminars and workshops on evolving trends as regards this concept of earnings management, for the management teams as well as impose sanctions on any non financial firm found to be involved in earnings management practices, to reduce this manace drastically in Nigeria. These will help build back investors confidence for investment purposes. Firms should also embark on massive innovative strategies in marketing, diversification and re-investing of their profits to increase capital for sustainability.